The Role of GPT Chat in Writing Scientific Articles: A Systematic Literature Review - Ruth Megawati; Hanida Listiani; Nuridin Widya Pranoto; Maik Akobiarek; Ruth Rize Paas Megahati S (Jurnal Penelitian Pendidikan IPA, 2023)
In general, the purpose of writing articles is to influence, educate, inform, convince, and entertain readers. Articles are usually published in media, such as bulletins, magazines, newspapers, or websites. Artificial intelligence is used to make scientific articles easier, namely GPT chat. The research aims to explain the role of GPT chat in writing scientific articles. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research examine that scientific articles themselves also consist of several types, namely research articles, non-research articles or review papers, and book reviews and obituaries. This open technology has several useful benefits for carrying out various daily tasks, namely: As a problem solver, answering difficult questions, completing math assignments and even essays, drafting articles, providing information, becoming a virtual assistant, working on coding, and helping customers. Service, Providing Suggestions, How to use chatGpt to write scientific articles starting from Preparing Research Materials, Brainstorming or Brainstorming sessions with ChatGPT, Conducting a literature review, Summarizing Research Articles, Gaps in the literature, Data analysis, Drawing outlines of Scientific Research papers, Editing and correcting scientific research, and Determine scientific research questions and edit and correct scientific research.